KORELASI KEPEMIMPINAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS PEMBELAJARAN DI ERA KURIKULUM MERDEKA DI SEKOLAH MADRASAH IBTIDAIYAH SWASTA DI PEKANBARU - Yundri Akhyar (Universitas Tribhuwana Tunggadewi, 2024)
The aim of this research is to find out whether there is a correlation between school principal leadership and learning effectiveness in their curriculum era at private Madrasah Ibtidaiyah schools in Pekanbaru. This research is quantitative research. This research involved 354 people, including teachers, school principals and students from four private Madrasah Ibtidaiyah located in the city of Pekanbaru. .Â Â As a research sample, respondents who are met by chance and are willing to participate will be taken by chance (accidental sampling method). After the data was collected, the Spearman Rank statistical technique was used to analyze the correlation between two variables using Spearman rho. The results of this research are that there is a positive correlation between school principal leadership and learning effectiveness in their curriculum era at private Madrasah Ibtidaiyah schools in Pekanbaru.